Inhibition of D-Ala:D-Ala ligase through a phosphorylated form of the antibiotic D-cycloserine - Sarah Batson (Nature Portfolio, 2017)
The antibiotic D-cycloserine (DCS) targets the peptidoglycan biosynthesis enzyme D-Ala-D-Ala ligase (Ddl). Here the authors reveal the DCS inhibitory mechanism by determining the structure of E. coli DdlB with a phosphorylated DCS molecule in the active site that formed in crystallo and mimics the D-alanyl phosphate intermediate.